Talking, Listening, and Teaching : a Guide to Classroom Communication. - Farrell, Thomas S. C. (SAGE Publications, 2009)
Using examples from real classrooms, this insightful book demonstrates how gathering and analyzing data about patterns in verbal and nonverbal classroom communication can boost the learning process.